(untitled) (Research, Society and Development, 2020)
Education is a right guaranteed to all, regardless of the subject’s physical and mental conditions. However, the right to enroll on their own does not guarantee the inclusion of students with disabilities in schools, requiring architectural adaptations, initial and continuing training aimed at special education and resources that meet the specificities of each discipline. The present study sought to carry out avant-garde work that permeated the teaching of Chemistry and visually impaired people in the context of the annals of three Brazilian Science / Chemistry teaching / education events, in the period from 2009 to 2019. In total, were mapped 74 papers, which were analyzed and discussed in four formulated categories, namely: Adequacy of strategies and teaching materials; Teacher training; Literature review and concepts about inclusion. From the results obtained, it can be concluded that there is a great concern for teachers and researchers to develop or adapt methodologies and teaching strategies for Chemistry for visually impaired students. However, there was a lack of papers that discussed the process of teacher training, at an initial or continued level, with a close eye on teaching chemistry to people with visual impairments. Another relevant point observed in this work suggests that teacher training significantly influences teachers’ conceptions about the teaching, learning and development process of students with visual impairment.